Advances in 3‐D electromagnetic focusing: Optimized time reversal and optimal constrained power focusing. Issue 1 (26th January 2017) - Iero, D. A. M.; Crocco, L.; Isernia, T.
Abstract: In this paper, we show how to successfully deal with the problem of focusing a vector field in a 3‐D scenario, by properly extending two recently introduced procedures developed with respect to 2‐D fields. In particular, to address this problem relevant in many applications, we describe an improved version of the well‐known time reversal technique, the optimized time reversal, and a procedure able to provide an optimal focusing in the presence of arbitrary upper bounds for the field intensity, the optimal constrained power focusing. The two approaches are presented, discussed, and comparatively assessed in two different scenarios representative of realistic working conditions. The results confirm the possibility of tackling the problem of focusing a 3‐D vector field in an efficient way and that the optimal constrained power focusing, while computationally heavier, provides the best possible focusing performance. Key Points: Focusing vector fields is a theoretical problem relevant to many applications, such as hyperthermia anticancer treatments Two optimized and efficient methods are discussed, the optimized time reversal (OTR) and the optimal constrained power focusing (OCPF) The methods allow to tackle the vector fields focusing problem in 3‐D scenarios in a computationally feasible and conceptually simple way